In vitro antibacterial activity of Sch 34343 and its stability to beta-lactamases and renal dehydropeptidase 1. - Matsuda, K (1985)
The in vitro antibacterial activity of Sch 34343 against 1,328 strains of clinical isolates was compared with those of imipenem and ceftazidime. Sch 34343 had a broad spectrum of antibacterial activity against both gram-positive and gram-negative bacteria but was inactive against Pseudomonas aeruginosa and Pseudomonas maltophilia. Sch 34343 was quite stable to hydrolysis by beta-lactamases, including both penicillinases and cephalosporinases. However, Sch 34343 was slightly hydrolyzed by a new type of beta-lactamase (oxyiminocephalosporin beta-lactamase), as was imipenem. Sch 34343 was slightly hydrolyzed by renal dehydropeptidase 1 but was somewhat more stable than other carbapenems.